Friction factor for newton and non newtonian fluid flow in curved pipes - SINGH, R. P.; MISHR, P. (My University, 1980)
The present work deals with the study of laminar and turbulent flow of Newtonian and non-Newtonian fluids flowing through helical and Archimedian spiral coils. By using a suitable viscosity expression corresponding to the shear stress prevailing at the wall, Newtonian correlations are shown to be applicable to a non-Newtonian fluid also. Relationships for spiral coils are developed from correlations for helical coils and are successfully compared with the data of Newtonian and non-Newtonian fluids. © 1980, The Society of Chemical Engineers, Japan. All rights reserved.